Dairy herd mastitis and reproduction: using simulation to aid interpretation of results from discrete time survival analysis - Hudson, Christopher D.; Bradley, Andrew J.; Breen, James E.; Green, Martin J. (Elsevier, 2015)
Probabilistic sensitivity analysis (PSA) is a simulation-based technique for evaluating the relative importance of different inputs to a complex process model. It is commonly employed in decision analysis and for evaluation of the potential impact of uncertainty in research findings on clinical practice, but has a wide variety of other possible applications. In this example, it was used to evaluate the association between herd-level udder health and reproductive performance in dairy herds.